Prevalence of microcephaly: the Latin American Network of Congenital Malformations 2010-2017 - Helen Dolk; Boris Groisman; Joan Morris; Rosa Pardo; Elizabeth Limb; Iêda M Orioli; Adriana Benavides-Lara; María de la Paz Barboza-Arguello; Maria Aurora Canessa Tapia; Giovanny Vinícius Araújo de França; Jorge Holguin; Paula Margarita Hurtado-Villa; et al. (BMJ Publishing Group, 2021)
Objective The Latin American Network of Congenital Malformations: ReLAMC was established in 2017 to provide accurate congenital anomaly surveillance. This study used data from ReLAMC registries to quantify the prevalence of microcephaly from 2010 to 2017 (before, during and after the Zika virus epidemic).Design Nine ReLAMC congenital anomaly registries provided case-level data or aggregate data for any live births, still births or terminations of pregnancy with microcephaly. Births to pregnant women infected with Zika virus first occurred in Brazil in 2015, and in the remaining registry areas in 2016 with the exception of Chile that did not experience Zika virus. Therefore the prevalence of microcephaly for 2010-2014 and individual years 2015, 2016 and 2017 was estimated using multilevel random effect Poisson models. Clinical classification and characteristics of the cases were compared pre and post Zika for all centres providing individual case-level data.Results The prevalence of microcephaly for all registries excluding Brazil was 2.3 per 10 000 (95% CI 2.0 to 2.6) for 2010-2014 rising to 5.4 (95% CI 4.8 to 6.0) in 2016 and 5.9 (95% CI 5.3 to 6.6) in 2017. Brazil had a prevalence of 0.6 per 10 000 (95% CI 0.5 to 0.6) in 2010-2014, rising to 5.8 (95% CI 5.6 to 6.1) in 2015, 8.0 (95% CI 7.6 to 8.3) in 2016 and then falling in 2017. Only 29 out of 687 cases of microcephaly were reported as congenital Zika syndrome in countries excluding Brazil.Conclusions The prevalence of microcephaly was influenced both by Zika causing congenital Zika syndrome and by increased reporting awareness.